Business micro- environment Challenges of Supply chain network integration: case study Jordan Industrial Estate Corporation - M.AIgaribeh, Assist .prof. Dr Khaled (IJRDO - Journal of Applied Management Science, 2017)
The purpose this of the study was to identify the challenges which Supply Chain networkintegration face in its implementation on both domestic and international firms, Classifyingthese Challenges depending on their effect, And finding relation between these classes inJordan Industrial Estate Corporation. The Questionnaires were sent to 140 employeesworking in the company. Only (124) were returned. The overall response rate for this studywas 92%. This is regarded as relatively high, since the respondents are managers and theywere supposed to be too busy to answer Questionnaire, Stratified random sampling was usedfor the research method: Beta , R , T-value .